Isohydricity and hydraulic isolation explain reduced hydraulic failure risk in an experimental tree species mixture - Moreno, Myriam; Simioni, Guillaume; Cochard, Hervé; Doussan, Claude; Guillemot, Joannès; Decarsin, Renaud; Fernandez-Conradi, Pilar; Dupuy, Jean-Luc; Trueba, Santiago; Pimont, François; Ruffault, Julien; Jean, Frederic; et al. (Plant physiology (Bethesda), 2024)
Abstract Species mixture is promoted as a crucial management option to adapt forests to climate change. However, there is little consensus on how tree diversity affects tree water stress, and the underlying mechanisms remain elusive. By using a greenhouse experiment and a soil-plant-atmosphere hydraulic model, we explored whether and why mixing the isohydric Aleppo pine (Pinus halepensis, drought avoidant) and the anisohydric holm oak (Quercus ilex, drought tolerant) affects tree water stress during extreme drought. Our experiment showed that the intimate mixture strongly alleviated Q. ilex water stress while it marginally impacted P. halepensis water stress. Three mechanistic explanations for this pattern are supported by our modeling analysis. First, the difference in stomatal regulation between species allowed Q. ilex trees to benefit from additional soil water in mixture, thereby maintaining higher water potentials and sustaining gas exchange. By contrast, P. halepensis exhibited earlier water stress and stomatal regulation. Second, P. halepensis trees showed stable water potential during drought, although soil water potential strongly decreased, even when grown in a mixture. Model simulations suggested that hydraulic isolation of the root from the soil associated with decreased leaf cuticular conductance was a plausible explanation for this pattern. Third, the higher predawn water potentials for a given soil water potential observed for Q. ilex in mixture can—according to model simulations—be explained by increased soil-to-root conductance, resulting from higher fine root length. This study brings insights into the mechanisms involved in improved drought resistance of mixed species forests.A mixture of trees with opposite drought response strategies (isohydric or anisohydric) greatly reduces the risk of hydraulic failure compared to monocultures.